DESAIN LANSKAP BOUTIQUE RESORT HOTEL DI CIMELATI SUKABUMI JAWA BARAT - Anwar, Dewi Rezalini; Ainul Yakin, Diajeng (Jurnal Lanskap Indonesia, 2016)
Resort Hotel is usually located in the mountains, on an island, or in some other exotic location away from the city. The concept of the resort is usually more integrated with nature. Boutique resort is one of resort types that shown Exoticism by strengthen the character of the place with adding accent alements of its architecture, interior and landscape. The character could be shown by some art in the landscape area that can be used to beautify the visual and give identity to the resort area. The purpose of this study are to identification the character of lansdcape boutique resort, to analyze and to make the synthesis from potentials and problems in site, and to make design concept of artworks display garden in resort area. The method that is used in this research is the method of Simond i.e commisioning, inventory, analysis, synthesis, concept design, construction, and implementation. The output of this study is site plan boutique resort for artworks display garden, area ilustration pictures in resort, perspective and section pictures, planting plan, detail design, and video. Manufacture of design base on suitable space for artworks placement wich can be reference for other resort in Indonesia, and it can be a space for displayed many artworks from many artists.